2009
DOI: 10.1080/17439760902933765
|View full text |Cite
|
Sign up to set email alerts
|

On being yourself in different cultures: ideal and actual self-concept, autonomy support, and well-being in China, Russia, and the United States

Abstract: The present study used multilevel modeling and measures of the Big Five to test Rogers' prediction that discrepancies between ideal and actual self-concept would be negatively associated with well-being, and to test the prediction drawn from self-determination theory that partners' autonomy support would be associated with smaller discrepancies. Discrepancies and well-being were found to be negatively associated in samples from the USA, Russia, and China, but participants' actual self-concept was closer to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 45 publications
10
102
0
2
Order By: Relevance
“…For example, in the present study, need imbalance was most related to negative affect, whereas interpretable cultural differences in wellbeing were mainly limited to the eudaimonic well-being scales. (Church et al, in press;Lynch et al, 2009;Sheldon, Ryan, Rawsthorne, & Ilardi, 1997).…”
Section: Need Satisfaction As a Predictor Of Well-beingmentioning
confidence: 99%
“…For example, in the present study, need imbalance was most related to negative affect, whereas interpretable cultural differences in wellbeing were mainly limited to the eudaimonic well-being scales. (Church et al, in press;Lynch et al, 2009;Sheldon, Ryan, Rawsthorne, & Ilardi, 1997).…”
Section: Need Satisfaction As a Predictor Of Well-beingmentioning
confidence: 99%
“…Empirically, autonomy (Lynch, La Guardia, & Ryan, 2009) as well as social relatedness (Decovic & Meeus, 1997) were both found to be essential determinants of a healthy self-concept, including academic self-concept.…”
Section: Current Studymentioning
confidence: 99%
“…Furthermore, research has identified cultural variations in educational practices and teachers' beliefs (TALIS 2009), as well as in many other psychological topics of interest for the AIED research community, such as decision making, reasoning, motivation, self-regulation, collaboration, competition, personal values, and various aspects of perception and interpretation (Henrich et al 2010a;Various authors 2010;Purdie and Hattie 1996;Lynch et al 2009;Ryan et al 2005;Hofstede 2008).…”
Section: Investigating the Socio-cultural Status Of Aied Researchmentioning
confidence: 99%